STRATEGI PENINGKATAN KUALITAS LAYANAN BERDASARKAN ANALISIS GAP DAN MODEL KANO PADA X CAFE - Ivanova, Beilla Aulia; Helianty, Yanti; Bakar, Abu (e-Proceeding FTI, 2024)
Mokopi is a café engaged in the culinary business. There are complaints taken from google reviews, such as the time the order is delivered too long, the cashier is not friendly, and parking is not spacious. In addition, there is competition for other cafes in the Antapani area. Based on these problems, research was conducted based on Gap Analysis with Dineserv dimensions that focused on restaurants. The goal is to measure the gap between what is expected and what consumers feel in the services provided and find out the cause of the problem. The Gap Analysis calculation will produce Gaps 5, 1, 2, and 3 where the negative Gap 5 calculation results will be integrated into the Kano Model. The purpose of using the Kano Model is to sort improvement priorities. The results of the calculation of Kano with must-be and one- dimensional categories will be made a top priority for improvement and improvement of service quality. Based on the calculation results of the Gap Analysis, there are 13 attributes with a negative Gap 5 result, meaning that all 13 attributes will be integrated into the Kano Model. The calculation of the Kano Model produces 3 attributes with must-be categories, meaning that these attributes need to be improved and are attributes that must be present in a company, otherwise consumers will not be satisfied. In addition, there are 8 attributes with one-dimensional categories, meaning that these attributes need to be improved so that consumers become satisfied, otherwise consumers will not be satisfied. The calculation results from the Gap Analysis and Kano Model will produce a strategy to improve service quality. Keywords: Dineserv, Gap Analysis, Negative 5 Gap, Kano Mode Mokopi adalah sebuah cafe yang bergerak pada bidang bisnis kuliner. Terdapat keluhan yang diambil dari google review, seperti waktu pesanan diantar terlalu lama, kasir yang kurang ramah, dan parkir yang tidak luas. Selain itu, adanya persaingan cafe lain di daerah Antapani. Berdasarkan permasalahan tersebut, maka dilakukan penelitian berdasarkan Analisis Gap dengan dimensi Dineserv yang memfokuskan kepada restaurant. Tujuannya untuk mengukur kesenjangan antara apa yang diharapkan dengan apa yang dirasakan oleh konsumen dalam layanan yang diberikan serta mengetahui penyebab permasalahan. Perhitungan Analisis Gap akan menghasilkan Gap 5, 1, 2, dan 3 dimana hasil perhitungan Gap 5 negatif akan diintegrasikan ke Model Kano. Tujuan digunakannya Model Kano untuk mengurutkan prioritas perbaikan. Hasil perhitungan Kano dengan kategori must-be dan one-dimensional akan dijadikan prioritas utama dilakukan perbaikan dan peningkatan kualitas layanan. Berdasarkan hasil perhitungan Analisis Gap,terdapat 13 atribut dengan hasil Gap 5 negatif, artinya ke-13 atribut tersebut akan diintegrasikan ke Model Kano. Perhitungan Model Kano menghasilkan 3 atribut dengan kategori must-be, artinya atribut tersebut perlu diperbaiki dan merupakan atribut yang harus ada dalam sebuah perusahaan, jika tidak maka konsumen tidak akan puas. Selain itu, terdapat 8 atribut dengan kategori one-dimensional, artinya atribut tersebut perlu ditingkatkan agar konsumen menjadi puas, apabila tidak maka konsumen tidak akan puas. Hasil perhitungan dari Analisis Gap dan Model Kano akan menghasilkan strategi peningkatan kualitas layanan. Kata kunci: Dineserv, Analisis Gap, Gap 5 negatif, Model Kano